Ultranarrow Graphene Nanoribbons toward Oxygen Reduction and Evolution Reactions. Issue 12 (6th November 2018) - Zhang, Jian; Sun, Yuanmiao; Zhu, Jiawei; Gao, Zhonghui; Li, Shuzhou; Mu, Shichun; Huang, Yunhui
Abstract: Identification of catalytic sites for oxygen reduction and evolution reactions (ORR/OER) is critical to rationally develop highly efficient bifunctional carbon‐based metal‐free electrocatalyst. Here, a unique defect‐rich N‐doped ultranarrow graphene nanoribbon with a high aspect ratio that exhibits excellent ORR/OER bifunctional activities and impressive long‐term cycling stability in Zn–air batteries is successfully fabricated. Density functional theory calculations indicates that the topological defects (e.g., pentagons and heptagons) cooperated with pyridinic‐N dopants on the edges are more favorable to electrocatalytic activity toward ORR and OER. This work provides a new design principle for carbon‐based electrocatalytic nanomaterials. Abstract : A unique defect‐rich and N‐doped ultranarrow graphene nanoribbon with high aspect ratio (DN‐UGNR) is successfully constructed. The DN‐UGNR catalyst reveals excellent oxygen reduction and evolution reactions bifunctional activities and impressive long‐term cycling stability in Zn–air batteries. Density functional theory results demonstrate that the topological defects cooperated with pyridinic‐N dopant are the most catalytically preferred active sites.